2009
DOI: 10.1159/000262295
|View full text |Cite
|
Sign up to set email alerts
|

Plasma β-Carotene Is Not a Suitable Biomarker of Fruit and Vegetable Intake in German Subjects with a Long-Term High Consumption of Fruits and Vegetables

Abstract: Background/Objective: β-Carotene is often used as a marker for the amount of fruit and vegetables consumed, but little is known about plasma β-carotene concentrations in subjects whose habitual (long-term) diets are characterized by different amounts of foods of plant origin. We compared dietary β-carotene intake and plasma concentrations in women on habitual diets differing in the consumed amounts of foods of plant origin. Methods: A comparison of dietary β-carotene intakes and plasma β-carotene concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…First, the change in b-carotene intake may be too small to be reflected in a significant change in plasma b-carotene concentration, possibly because of the high intra-and interindividual variations in both the intake and plasma concentration of b-carotene (55). In addition, in intervention studies where significant responses have been observed, increases in b-carotene intake were greater (31,33), and although it would be expected that such an increase would increase concentration, it may not because of variations in the bioavailability of b-carotene from different diets (34). Moreover, in addition to b-carotene, other carotenoids, such as a-carotene, lutein, b-cryptoxanthin, lycopene, and zeaxanthin, have been recommended for use as biomarkers for fruit and vegetable intake (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the change in b-carotene intake may be too small to be reflected in a significant change in plasma b-carotene concentration, possibly because of the high intra-and interindividual variations in both the intake and plasma concentration of b-carotene (55). In addition, in intervention studies where significant responses have been observed, increases in b-carotene intake were greater (31,33), and although it would be expected that such an increase would increase concentration, it may not because of variations in the bioavailability of b-carotene from different diets (34). Moreover, in addition to b-carotene, other carotenoids, such as a-carotene, lutein, b-cryptoxanthin, lycopene, and zeaxanthin, have been recommended for use as biomarkers for fruit and vegetable intake (33).…”
Section: Discussionmentioning
confidence: 99%
“…They are generally found in plant foods, mainly yellow and orange fruits, orange root vegetables, and green leafy vegetables. Population studies have indicated that b-carotene may be a reliable biomarker for the intake of fruits and vegetables (33), although not all studies agree (32,34). In addition to being a possible biomarker of dietary intake, plasma b-carotene is linked as a risk factor for diseases as previously reviewed (35).…”
Section: Introductionmentioning
confidence: 98%
“…Fruit and vegetable intake patterns may also lead to differential results in biomarker levels (45) . Such markers are also affected by numerous physiological factors beyond dietary intake (46) .…”
Section: Issue 1: What Counts Towards Fruit and Vegetable Intake?mentioning
confidence: 99%
“…Measurement of certain biomarkers such as plasma carotenoids is also used to indirectly assess fruit and vegetable intake in individuals although such measurements tend to be quite specific to certain types or categories of fruits and vegetables and are not necessarily good for evaluating overall fruit and vegetable intake ( 44 ) . Fruit and vegetable intake patterns may also lead to differential results in biomarker levels ( 45 ) . Such markers are also affected by numerous physiological factors beyond dietary intake ( 46 ) .…”
Section: Issues With Defining and Measuring Intakementioning
confidence: 99%
“…Our results are in line with those suggesting that plasma β-carotene concentrations may not reflect β-carotene intake and the amount of fruits and vegetables consumed. In a study carried out in 514 women adhering to an average western diet ( n = 172), wholesome nutrition (following preventive recommendations, n = 238) or a raw food diet ( n = 104), it was observed that plasma β-carotene concentrations (1.07 ± 0.14, 1.65 ± 0.15, and 1.16 ± 0.16 μmol/L, respectively) did not reflect the mean β-carotene intake (5.5 ± 0.2, 9.3 ± 0.3, and 14.7 ± 0.7 mg/day, respectively) [47]. Similarly, when the post-intervention fasting plasma carotenoid levels were analyzed in a group of 155 men and 109 women who participated in 6 fully controlled dietary interventions, the daily fruit and vegetable intake was not associated with plasma β-carotene [48].…”
Section: Discussionmentioning
confidence: 99%